DETERMINATION OF ADSORPTION KINETICS OF COCONUT HUSK ADSORBENT FOR HEAVY METALS REMOVAL USING LANGMUIR AND FREUNDLICH ISOTHERM EXPRESSIONS - L, Sirajo; L., Musa; I. A., Ndanusa (International Journal of Research -GRANTHAALAYAH, 2018)
Adsorption of heavy metal cationic ions (Cr, Pb, and Cu) onto coconut husk carbon (CHC) adsorbent has been studied using batch-adsorption method. The study was carried out to investigate the adsorption kinetic and adsorption isotherm of the coconut husk adsorbent for the removal of heavy metals in waste liquid effluent. The influence of pH, contact time, adsorbent dose, and adsorbent concentration, and temperature on the adsorption process was also studied. Results indicated an initial increase in adsorption rate, and optimal removal of heavy metal was reached within 70 minutes, further increase in contact time and temperature show significant change in equilibrium concentration. Also, further increase in adsorbent dosage revealed significant change in the sorption capacity of the CHC. The adsorption isotherms could be fitted well by both Langmuir and Freundlich models. The RI (equilibrium parameter) value in the present investigation was less than 1 (one) which indicates that the adsorption of the heavy metals ions on the CHC is favorable. The value of n for this study which indicates the degree of non-linearity between solution concentration and adsorption were 0.31–0.39, this result indicated that the adsorption of heavy metals onto the CHC is a chemical sorption. After treatment of synthetic heavy metal solution with the CHC, the adsorption isotherm model analysis revealed that the adsorption capacity (b) of CHC for the heavy metal were 89 mg/L (Cr), 125.5 mg/L (Pb), and 129.7 mg/L (Cu). Conclusively, the results indicate that the freely abundant agricultural waste-coconut husk can be treated for heavy metal adsorption but it’s not economically viable because it’s not renewable due to the chemisorption nature of the adsorption process.